KETIDAKSADARAN PENGARANG DALAM NOVEL SUNYARURI: TINJAUAN PSIKOLOGI SASTRA - Viola Yngwie Oriordan; Arum Melati; Dwi Susanto (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Psychological problems that affect behavior towards others are a phenomenon that occurs in human life. This is experienced by the character Risa in her novel Sunyaruri by Risa Saraswati. The events she experienced made Risa behave according to what she saw. Her environment affects the behavior of Risa's character in dealing with psychological conflicts. The purpose of this research is to describe the form of Risa Saraswati's psychological unconscious as an indigo. This research uses a literary psychology approach, especially Sigmund Freud's psychology. Based on the research results, through condensation and symbolization, metaphors of sadness, metaphors of friends, metaphors of longing, and metaphors of loneliness were found. Meanwhile, through diversion, talent metonymy was found. Risa's behavior is a response to stimuli captured psychologically.